CONTRASTING GENDER BIAS LANGUAGES IN PHILIPPINES AND U.S ONLINE NEWS ARTICLES: A CORPUS-BASED STUDY - Kharl Vincent C. Requinala; Jessa Folloso; Robertt Ross Almazan; Mark Philip Paderan (Program Studi Tadris Bahasa Inggri Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2022)
This study aimed to explore the most prevalent gender-biased languages and to identify what type of rhetorical devices were used frequently in the Philippines and U.S Online News Articles and to highlight the similarities and differences of rhetoric taken from ten online news websites. The corpus is made up of 20 articles per news outlet which are GMA News, Manila Bulletin, Manila Times, Rappler, and Philippine Daily Inquirer from the Philippines. Politico, LA Times, The Guardian, USA Today, and CBN News from US. All news was contrastively analyzed based on Robert Kaplan’s Theory of Contrastive Rhetoric using AntConc software. The findings revealed that there are rhetorical devices found in these articles to filter the used labels for males and females that invoke stereotyping. Results also revealed that both countries are similar in terms of using positive and nice words subtly on describing women. However, a vast contradiction is also depicted due to the fact that news writers utilize words that negatively connote and has a sharp definition that is associated with women. Thus, the study concludes that there should be widespread information and practice about the usage of Gender Fair Language in various professions most especially in Media and Journalism.